Recovery in the residential school abuse aftermath : a new healing paradigm - Dionne, Dee; University of Lethbridge. Faculty of Health Sciences (Lethbridge, Alta. : University of Lethbridge, Faculty of Health Sciences, c2008., 2009)
This qualitative study informs the literature by bringing two perspectives together: the trauma of residential school abuse and the transpersonal viewpoint of healing. A phenomenological hermeneutic approach explored lived experiences of residential school survivors and their families. Transpersonal psychology was introduced as the focus for a new healing paradigm. The research questions ask, “What has been the lived experience of the trauma of residential school abuse” and “How are traditional and non-traditional healing practices mutually applied in the recovery process by individuals who are impacted by the residential school experience”? Five First Nations co-researchers were interviewed, the data was analyzed, coded, and a thematic analysis was undertaken from which six themes emerged. The results of this study may go on to employ this new healing paradigm to help First Nations people gain spiritual wholeness. Finally, a description and summary of research findings, limitations and implications for counselling were discussed. x, 193 leaves 29 cm. --